Memory Through Sahrawi Oral Poetry: The Path to Cultural Emancipation in Morocco - koumani, Abdesallam (International Journal of Language and Literary Studies, 2025)
This paper examines Sahrawi Hassani oral poetry as a vital site for negotiating cultural memory, identity, and resistance in Morocco’s Saharan regions. Drawing on memory studies and border-poetics theory, it argues that Hassani’s verse operates as a living cultural archive that challenges colonial narratives portraying the Sahara as separate from Morocco. The study situates Hassani poetry within its nomadic origins—performances under the khaima (tent) that transmitted genealogies, moral codes, and heroic histories—and shows how these verses historically resisted Spanish colonial strategies that exploited local customs to legitimize territorial separation in Rio de Oro and Sidi-Ifni. The paper reviews existing scholarship (Deubel, Lopez Martin, Bubrik, among others) and highlights its own contribution by foregrounding the shared cultural heritage and political bordering processes that shape Sahrawi identity. It further analyzes the digital transformation of this oral tradition, demonstrating how YouTube festivals, such as Khaymat al-Shi?r and Layali Azawan al-Sahra, reterritorialize memory in virtual space and expand their audience to diasporic and global communities.